The Effect of Teacher Professional Competence on Student Learning Achievement at MAN 3 Tangerang - Abdul Wahid; Siti Asiah; Miftahul Huda; Arkam Lahiya; Najamuddin Petta Solong (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
This study aims to analyze the effect of teacher professional competence on student learning achievement at MAN 3 Tangerang and to determine to what extent teacher professional competence influences student learning achievement. In this study, the researchers applied a quantitative approach with a survey method and employed simple linear regression in answering the hypothesis. Data were collected using a questionnaire, in which samples were selected using a simple random sampling technique, resulting in 170 students. The questionnaire applied a Likert scale with four alternative answers. Based on the results of data processing and calculation using SPSS v. 22, statistical testing indicated that Ho was rejected and Ha was accepted, meaning that teacher professional competence significantly influences student learning achievement. It was derived from the results of the t-test presenting a t-count of 6.682 which is > t-table (i.e., 1.974) with a significance value of 0.000 (< 0.05 or 5%). Furthermore, the results in ANOVA also supported the acceptance of Ha, in which the obtained value of significance was 0.000 (< 0.05). Therefore, this study revealed that teacher professional competence influences student learning achievement. Moreover, the results of the coefficient of determination showed that the variable of teacher professional competence can explain the variable of student learning achievement by 20%. Meanwhile, the remaining 80% is explained by other variables not examined in this study.